KEANEKARAGAMAN TUMBUHAN OBAT MASYARAKAT DI HUTAN TALANG RENCONG DESA PULAU SANGKAR, KABUPATEN KERINCI, JAMBI: Diversity of Medicinal Plants in The Forest Talang Rencong Village Island Cage, Regency Kerinci, Jambi - Ade Adriadi; Nursanti Nursanti; Rike Puspitasari (Media Konservasi, 2020)
Indonesia has approximately 30,000 species of medicinal plants based on the richness of the flora. Indonesia has the great potential to develop herbal products that are equivalent to modern medicine. The modern treatment has not been reachable by the whole community in Indonesia, only about 25% affordable and the rest are not yet affordable. The role of traditional medicine recipes become much helpful especially for people living in remote areas with minimal access. The research was conducted in April-May 2019 at Talang Rencong Traditional forest, Pulau Cage Village, Kerinci Regency, Jambi. The sample area of research was 1 Ha, or 5% of total area. The methods used in this research were participatory exploration and observation, data collection was conducted by tracing indigenous forests accompanied by local communities (Data is analyzed from any species found during research). The research in the indigenous forest Talang Rencong village Pulau Cage, Kerinci Regency, Jambi acquired 23 familia and 39 species of medicinal plants used. How to use from the herbs are divided into 25 species of medicinal plants that use drinkable, 6 species of medicinal plants are applied or pasted, 4 species of herbs are directly consumed, 1 species of medicinal plants is used to be washed, 2 species of medicinal plants used to be dipped in the eyes and 1 type of medicinal plants that use the input into perforated teeth The benefits of such medicinal plants are as breast cancer medicine, relieves itching for children, nail health remedy, uric acid medecine, removal bruising, uterine watering, appetite enhancer, diarrhea, toothache medications, jaundice medications, cough medicines, shortness of breath medication for infants, deep heat medications, reducing blood sugar levels, paralysis medications, lowering cholesterol, and medication for postnatal blood and uric acid. Keywords: ethnobotany, medicinal plants, Rencong customary forest